Evaluating students’ autonomous learning through their uses of a self-access centre - Posada Ortiz, Julia Zoraida (Colombian Applied Linguistics Journal, 2006)
This article describes a small-scale project aimed at developing a systematic evaluation of a Self Access Centre (SAC) located at a private university in Bogotá. The objectives of the project were first, to identify the most common strategies used by the SAC’s users and find out if this SAC was enhancing autonomy. The second objective was to discover some of the strengths and weaknesses of the SAC. The results showed that students used indirect strategies which might show some autonomy, since these strategies are related to the management of our own language learning. The results also demonstrated that students need some counselling with both the language and technology.